Therapeutic Hypothermia for Neonatal Encephalopathy Results in Improved Microstructure and Metabolism in the Deep Gray Nuclei - Bonifacio, S.L.; Saporta, A.; Glass, H.C.; Lee, P.; Glidden, D.V.; Ferriero, D.M.; Barkovich, A.J.; Xu, D. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Therapeutic hypothermia has reduced morbidity and mortality and is associated with a lower burden of lesions on conventional imaging in NE. However, its effects on brain microstructure and metabolism have not been fully characterized. We hypothesized that therapeutic hypothermia improves measures of brain microstructure and metabolism. MATERIALS AND METHODS: Forty-one neonates with moderate/severe NE (29 treated with hypothermia, 12 nontreated) and 12 healthy neonates underwent MR imaging, DTI, and 1H-MR spectroscopy. MR imaging scans were scored by the predominant pattern of brain injury: normal, watershed, and BG/thalamus. ADC, FA, Lac:NAA, and NAA:Cho values from bilateral BG and thalamus ROIs were averaged. T test and linear regression analysis were used to determine the association between hypothermia and MR imaging quantitative measures. RESULTS: Conventional MR imaging findings were normal in 41% of treated neonates; all nontreated neonates had brain injury. Values of MR imaging metrics were closer to normal in treated neonates compared with nontreated neonates: ADC was 63% higher in the BG and 116% higher in the thalamus (both P < .05), and Lac:NAA was 76% lower (P = .04) in the BG. Treated neonates with normal MR imaging findings had normal 1H-MR spectroscopy metabolites, and ADC was higher by 35% in the thalamus (P = .03) compared with healthy neonates. CONCLUSIONS: Therapeutic hypothermia may reduce disturbances of brain metabolism and preserve its microstructure in the setting of NE, possibly by minimizing cytotoxic edema and cell death. Long-term follow-up studies are required to determine whether early post-treatment DTI and 1H-MR spectroscopy will be useful biomarkers of treatment response. BGbasal gangliaCIconfidence intervalFAfractional anisotropyLaclactateNEneonatal encephalopathyWSwatershed